Utilization of Ministry of Health Medication Return Programme, Knowledge and Disposal Practice of Unused Medication in Malaysia - Yang, Su Lan; Ling Tan, Sze; Goh, Qing Liang; Yen Liau, Siow (Journal of Pharmacy Practice and Community Medicine)
Objective: (1) To report the awareness on MRP and its utilization rate. (2) To assess environment awareness with regards to improper disposal. (3) To explore practices toward unused medication. Methods: A cross-sectional study was conducted in 33 out-patient pharmacies in Sabah healthcare facilities. Quota sampling was used to recruit 244 subjects. Data collector from each facility was identified and trained prior to data collection. Self-reporting questionnaire captured data of socio-demographic, awareness on MRP and patient’s knowledge and practice towards unused medication. Independent t-test and chi square test were performed to detect differences and association. Result: Subject mean (SD) age was 45.1(15.5) years and almost two-third (60%) of the subjects were female. Majority (73%, 95%CI 67- 78%) knew that inappropriate disposal of medication will cause environmental hazard. Only 54% (95% CI 47-60%) had heard of MRP, 26% (95%CI 21-32%) had utilized MRP to return unused medication. Subject’s awareness on environmental hazard and MRP were associated with their practice to return unused medication (p=0.001 and p<0.001 respectively). Mean years of education and median family income were significantly different between the aware and unaware group respectively [11.3(6.0) vs 8.9(4.5) yrs, p=0.003; RM2000 vs RM1260, p<0.001]. The most common unused medication were analgesics (27.1%), antihypertensive (24.4%), antiglycemic (14.7%) and supplements (12%). The two predominant methods to “dispose” unused medication at home were through garbage (47.8%) and return to healthcare facilities (30.0%). Conclusion: This study has established the evidence for public awareness on MRP, environment awareness and disposal practice of Malaysian citizen. Creative and innovative recommendations have been made for MRP promotion and to improve public knowledge on safety disposal of unused medication.
Keywords: Medication return programme; Pharmacy service; Unused medication; Knowledge; Disposal; Malaysia